Enhancing indigenous peoples’ participation in climate policy processes - Hellin, Jon; Fisher, Eleanor; Ng’endo, Mary; Loboguerrero, Ana María; Ohenjo, Nyang’ori; Rose, Sabrina (2024)
PLOS Climate has published several Opinion articles about Indigenous People’s active participation in climate change processes. We build on these by stressing the importance of a more granular approach to climate justice and Indigenous Peoples’ participation in climate policy processes. We argue that a more explicit focus on and context-specific understanding of social equity allows for greater participation of the most vulnerable within Indigenous communities. This necessitates attention to historical and contemporary relations of power and oppression, ones that frame the lives of Indigenous Peoples worldwide. By implication, it mitigates the dangers of maladaptation within these communities and gives greater credence to the pledge to leave no one behind. The importance of social equity highlights a key research development and evidence gap ahead of the 2024 Conference of the Parties (COP) of the UNFCCC (COP29).